The influence of transformational leadership, work environment and workload on employee performance at ATR BPN Bengkulu City - Ramadhan, Andra; Widodo, Slamet (Institute of Computer Science (IOCS), 2023)
In facing the era of globalization, companies need to operate more efficiently and effectively both internally and externally. And performance is one way a company can increase its value. This research aims to determine the variables that influence employee performance, with special emphasis on workload, work environment, and transformational leadership. This research, which used a sample of 70 respondents and a quantitative methodology using primary data, was carried out at the ATR BPN office in Bengkulu City. However, workload does not affect their performance significantly